2013
DOI: 10.2478/acas-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Sheep wool and leather waste as fertilizers in organic production of asparagus (Asparagus officinalis L.) / OVČJA VOLNA IN OSTRUŽKI USNJA KOT GNOJILI V EKOLOŠKI PRIDELAVI ŠPARGLJA (Asparagus officinalis L.)

Abstract: 1 univ. dipl. inž agr.; Biotehniška fakulteta, Oddelek za agronomijo, Jamnikarjeva 101, SI -1111 Ljubljana, Slovenija 2 doc.dr.; Biotehniška fakulteta, Oddelek za agronomijo, Jamnikarjeva 101, SI -1111 Ljubljana, Slovenija; rok.mihelic@bf.uni-lj.si Acta agriculturae Slovenica, 101 -2, september 2013 str. 191-200 COBISS Code 1.01 DOI: 10.2478DOI: 10. /acas-2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…Generally, the present field observations were supportive of our previous pot study. The preceding pot experiment (Vončina and Mihelič, 2013), supported the authors’ field observations where sheep wool proved to be a good source of N. Similarly, Galvez et al (2012) observed that in both field as well as laboratory studies a significant fraction of available N was released in the first 30 days after application.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Generally, the present field observations were supportive of our previous pot study. The preceding pot experiment (Vončina and Mihelič, 2013), supported the authors’ field observations where sheep wool proved to be a good source of N. Similarly, Galvez et al (2012) observed that in both field as well as laboratory studies a significant fraction of available N was released in the first 30 days after application.…”
Section: Resultssupporting
confidence: 64%
“…Fishery waste, feather meal and seabird guano showing mineralization (Hartz et al, 2010) had lower C/N ratios compared with Biolyzer (Hartz et al, 2010) showing immobilization. In yet another study authors observed mineralization and nitrification of organic N from sheep wool waste which was richer in organic N (over 5%) than manure and compost (Vončina and Mihelič, 2013). The C/N ratio of tithonia was lower than maize and thus had a quicker mineralization rate (Gentile et al, 2011).…”
Section: Resultsmentioning
confidence: 99%